Development of an educational programme to facilitate critical thinking of student nurses in Namibia - Pretoruis, Louise; Van Dyk, Agenes; Small, Luis; Amukugo, Hans Justus (International Journal of Advanced Nursing Studies, 2016)
The article focused on the development process of an educational programme to facilitate the development of critical thinking in the students. The study was conducted in four phases, beginning with the needs assessment in phase 1 through which the researcher determine the need of the students in terms of critical thinking. The deductive data analysis of phase 1 served as basis of the conceptual framework for the development of an educational programme. Phase 2 focused on the development of the conceptual framework and it was achieved by utilized a specific educational approaches and philosophical framework were employed. Phase 3 and 4 were conducted simultaneously. Phase 3 focuses on implementation while phase 4 focuses on evaluation. A quasi – experimental design was implemented which focused on active participation by the participants in the programme.